The effect of pre-treatment on the thermal performance of fly ash geopolymers - Rickard, William; Borstel, C.; Van Riessen, Arie (Elsevier Science, 2013)
This paper presents a study on the thermal behaviour of fly ash geopolymers that have been pre-treated prior to thermal exposure. Thermal and mechanical analysis was conducted on geopolymers that were leached in water and gradually dried and the results were compared to untreated samples. The aim of the pre-treatment was to remove the water and the excess alkali without damaging the structure prior to high temperature exposure. Fast dehydrating water is known to damage geopolymers by inducing cracks. Alkalis are known to be network modifiers and as such, where in excess, reduce the melting point of aluminosilicate glasses. It was found that the pre-treatment produced samples with negligible thermal expansion up to 700 °C and less damage associated with dehydration which increased their post firing compressive strength. The pre-treated geopolymer panel had a marginally shorter fire rating than the as-cured sample though it exhibited greater resistance to cracking and slower post dehydration temperature increases.